Sport Tourism and the Economic Multiplier Effect: A Critical Review of Marathon Events and the Structural Challenges of Large-Scale Sport Event Management in Indonesia - Ni Kadek Swandewi; I Gusti Ayu Ratih Asmarani; Luh Putu Citrawati (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: This study aims to critically examine how marathon events generate economic multiplier effects, identify the structural factors that limit these mechanisms in Indonesia, and propose strategic directions to strengthen marathon-based sport tourism. Method: This research employs a critical literature review using peer-reviewed sources from Scopus, Web of Science, Google Scholar, and ResearchGate. The review synthesizes 29 key references on sport tourism, economic impact, sustainability, governance, and destination branding. Thematic synthesis is used to analyse how multiplier effects operate and why they often underperform in the Indonesian context. Result: The findings reveal three major themes. First, marathon events theoretically generate economic benefits through direct spending, supply-chain activation, induced income circulation, and long-term destination branding. Second, these mechanisms are constrained in Indonesia by leakage to non-local firms, weak MSME integration, short visitor stays, displacement effects, governance fragmentation, and limited community acceptance. Third, the study highlights strategic pathways including evidence-based evaluation, stronger local procurement, improved multi-stakeholder governance, enhanced participant experience, and community-driven branding to maximize economic outcomes. Contribution: This study advances knowledge by integrating economic, governance, sustainability, and branding perspectives to explain why Indonesian marathon events yield modest multiplier effects. The review provides policymakers and event organizers with practical frameworks to improve event planning, strengthen local economic linkages, and support sustainable tourism development. It fills a gap in the literature by offering a structured, context-specific analysis of marathon events in an emerging tourism economy.